Предмет: Алгебра,
автор: ivanluki
Выполните действия:
в) (2a-3c)(a+2c)
г) (y-1)(y^2+2y-4)
д) (3x^3-6x^2):3x^2
Ответы
Автор ответа:
0
(2а-3с)(а+2с)=2а² +ас -6с²
(у-1)(у²+2у-4)= у³+2у²-4у-у²-2у+4=у³ - 6у+4
(3х³ -6х²):3х²=3х³/3х² - 6х²/3х²=х -2
(у-1)(у²+2у-4)= у³+2у²-4у-у²-2у+4=у³ - 6у+4
(3х³ -6х²):3х²=3х³/3х² - 6х²/3х²=х -2
Похожие вопросы
Предмет: Алгебра,
автор: merolinvlad
Предмет: Английский язык,
автор: gavronskanatala
Предмет: Математика,
автор: yaryy12
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: mariyka6